Contactless active mirror for space telescopes - Briguglio, Runa (Il Colle di Galileo, 2024)
The SPLATT project is a technological research activity funded by INAF, in the field of primary active mirrors for next generation space telescopes. The goal is to demonstrate that active mirrors with contactless actuators are insensitive to disturbance from the telescope and can therefore be key-elements in the reduction of complexity and cost. Keywords: space telescopes, active mirror, active optics, LUVOIR.